A view on nursing in Rwanda: story of a teaching experience - Isabel Casabona Martínez; Manuel Lillo Crespo; María Dolores Mora Antón; Sara Cort Casabona (Universidad de Alicante, 2012)
The present article aims to give expression to a personal experience that I had as a teaching nurse collaborating in a co-operation for development project, giving specialised training to a group of nurses in Nemba hospital, in Rwanda.